Materials science and metallurgy - Pollack, Herman W. (Virginia : Prentice- Hall Company, 1981)
The third edition of this book contains several changes suggested in a critical review of the second edition. The intention of this textbook in every sense of the word.
Chapter 1. The production of ferrous and nonferrous metals -- Chapter 2. The structure of metals -- Chapter 3. Inspection and testing of materials -- Chapter 4. Equilibrium diagrams -- Chapter 5. The iron-iron carbide diagram: steel -- Chapter 6. The iron-iron carbide diagram: cast iron -- Chapter 7. Classification of steels -- Chapter 8. Heat-treating of steel -- Chapter 9. Tool steels -- Chapter 10. Nonferrous light metals -- Chapter 11. Nonferrous heavy metals -- Chapter 12. Corrosion -- Chapter 13. Plastics -- Chapter 14. Rubber -- Chapter 15. Adhesives -- Chapter 16. Ceramic materials -- Chapter 17. Cement and concrete -- Chapter 18. Wood and paper.
Keywords: METALS